2013
DOI: 10.1093/qjmed/hct183
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring trends in recreational drug use from the analysis of the contents of amnesty bins in gay dance clubs

Abstract: This study has provided a snapshot of the pattern of drug use in the gay community which compliments findings of the self-reported surveys and other studies from the same population. The information obtained will be helpful in guiding in designing harm reduction interventions in this community and for monitoring the impact of changes in legislation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…On the contrary, a very high consumption was highlighted for cocaine, followed by cannabis and other substances commonly rubricated as “club drugs” (ketamine, ecstasy, methamphetamine) [2, 3]. These results contrast with other studies on the recreational drug scene in the UK, which reported a fairly significant consumption of mephedrone [18–20], Gamma-butyrolactone (GBL) [21], and amyl nitrite [20]. Our results are more similar to reports on the nightlife scenes of US [22] and continental Europe [23].…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, a very high consumption was highlighted for cocaine, followed by cannabis and other substances commonly rubricated as “club drugs” (ketamine, ecstasy, methamphetamine) [2, 3]. These results contrast with other studies on the recreational drug scene in the UK, which reported a fairly significant consumption of mephedrone [18–20], Gamma-butyrolactone (GBL) [21], and amyl nitrite [20]. Our results are more similar to reports on the nightlife scenes of US [22] and continental Europe [23].…”
Section: Discussionmentioning
confidence: 99%
“…Despite being banned, mephedrone remains available for illicit recreational consumption (Ayres and Bond, 2012;Van Hout and Brennan, 2012;Yamamoto et al, 2013;Salomone et al, 2015) and many users have compared its psychostimulant effects to those of MDMA and cocaine (Kelly et al, 2013;. Since caffeine produces marked enhancement of the adverse effects of MDMA we have now examined whether it also alters the pharmacological changes associated with mephedrone administration.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the ever use of GHB/GBL by 15-16 year old students in 12 EU countries was 0.5-1.4%. There are, however, a number of subpopulations, like homosexuals, gay disco's, night clubs, and dance and music settings where GBL use is considerable (Hunter et al, 2014;Wood et al, 2009Wood et al, , 2012Yamamoto et al, 2013). A survey of the clubbers magazine 'MixMag' carried out in 2010 in the UK showed a lifetime prevalence of GHB and GBL use of 11.8% and 5.6%, respectively (Winstock and Power, 2011).…”
Section: Prevalence Of Usementioning
confidence: 99%
“…Another study performed in 2010 in the UK Lund et al (1965) showed that the last month prevalence of GBL in two 'gay-friendly' dance clubs was 19% (Wood et al, 2012). Of 544 samples retrieved in drug amnesty bins of gay-friendly nightclubs in South London, 160 (29.4% of total) contained GBL, whereas the remaining 38% of the liquid samples contained GHB (Yamamoto et al, 2013). Both in the UK (EMCDDA, 2008) and Sweden (Mickelsson, 2005), the use of GBL increased following the ban of GHB in 2000.…”
Section: Prevalence Of Usementioning
confidence: 99%
See 1 more Smart Citation